ÁGUA SUBTERRÂNEA COMO REFORÇO NO ABASTECIMENTO DA SEDE MUNICIPAL DE BUÍQUE/ PE - Costa Filho, Waldir D.; Galvão, Manoel Júlio da T. G.; Pires, Saulo de T. M.; Rocha, Dunaldson Eliezer G. A. da; Oliveira, Roberto G. de; Amaral, Cristiano de A.; Temóteo, José Wilson de C.; Lima, Enjôlras de A. M.; Silva, José Carlos da (Águas Subterrâneas, 2001)
Resumo não disponível.